Particle tracking modeling of sediment-laden jets - S. N. Chan; J. H. W. Lee (Advances in Geosciences, 2014)
This paper presents a general model to predict the particulate transport and deposition from a sediment-laden horizontal momentum jet. A three-dimensional (3-D) stochastic particle tracking model is developed based on the governing equation of particle motion. The turbulent velocity fluctuations are modelled by a Lagrangian velocity autocorrelation function that captures the trapping of sediment particles in turbulent eddies, which result in the reduction of settling velocity. Using classical solutions of mean jet velocity, and turbulent fluctuation and dissipation rate profiles derived from computational fluid dynamics calculations of a pure jet, the equation of motion is solved numerically to track the particle movement in the jet flow field. The 3-D particle tracking model predictions of sediment deposition and concentration profiles are in excellent agreement with measured data. The computationally demanding Basset history force is shown to be negligible in the prediction of bottom deposition profiles.